Agile Software Development: Adaptive Systems Principles and Best Practices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software development methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS principles and three dimensions (product, process, and people) results in several recommendations for “best practices” in systems development.
Keywords: IMPORTANT

Complexity Leadership Theory: An Interactive Perspective on Leading in Complex Adaptive Systems - Lichtenstein, Uhl-Bien; Schreiber, Orton; Lichtenstein, Benyamin; Uhl-Bien, Mary; Marion, Russ; Seers, Anson; Orton, James Douglas; Schreiber, Craig (Emergence, 2006)
Traditional, hierarchical views of leadership are less and less useful given the complexities of our modern world. Leadership theory must transition to new perspec-tives that account for the complex adaptive needs of organizations. In this paper, we propose that leadership (as opposed to leaders) can be seen as a complex dynamic process that emerges in the interactive "spaces between" people and ideas. That is, leadership is a dynamic that transcends the capabilities of individuals alone; it is the product of interaction, tension, and exchange rules governing changes in per-ceptions and understanding. We label this a dynamic of adaptive leadership, and we show how this dynamic provides important insights about the nature of leadership and its outcomes in organizational fields. We define a leadership event as a perceived segment of action whose meaning is created by the interactions of actors involved in producing it, and we present a set of innovative methods for capturing and analyzing these contextually driven processes. We provide theoretical and practical implications of these ideas for organizational behavior and organization and management theory.

Planners versus Searchers in Foreign Aid - Easterly, William (Asian Development Review, 2006)
Only for the recipients of foreign aid is something akin to central planning seen as a way to achieve prosperity. The end of poverty is achieved with free markets and democracy—where decentralized “searchers” look for ways to meet individual needs—not Poverty Reduction Strategy Papers (PRSPs) to achieve Millennium Development Goals (MDGs). The PRSPs and MDGs create lots of bureaucracy but hold no one specific agency in foreign aid accountable for any one specific task. Planners in foreign aid use the old failed models of the past—the “Financing Gap”, the “poverty trap”, the government-to-government aid model; and the “expenditures = outcomes” mentality. Searchers in foreign aid would imitate the feedback and accountability of markets and democracy to provide goods and services to individuals until homegrown markets and democracy end poverty in the society as a whole. An example of the more promising “searchers” approach in foreign aid is 2006 Nobel Peace Laureate Mohammad Yunus and Grameen Bank.

Resilience Thinking: Sustaining Ecosystems and People in a Changing World - Walker, Brian; Salt, David; Reid, Walter V. (Island Press, 2006)
Increasingly, cracks are appearing in the capacity of communities, ecosystems, and landscapes to provide the goods and services that sustain our planet's well-being. The response from most quarters has been for "more of the same" that created the situation in the first place: more control, more intensification, and greater efficiency. "Resilience thinking" offers a different way of understanding the world and a new approach to managing resources. It embraces human and natural systems as complex entities continually adapting through cycles of change and seeks to understand the qualities of a system that must be maintained or enhanced in order to achieve sustainability. It explains why greater efficiency by itself cannot solve resource problems and offers a constructive alternative that opens up options rather than closing them down. In "Resilience Thinking", scientist Brian Walker and science writer David Salt present an accessible introduction to the emerging paradigm of resilience. The book arose out of appeals from colleagues in science and industry for a plainly written account of what resilience is all about and how a resilience approach differs from current practices. Rather than complicated theory, the book offers a conceptual overview along with five case studies of resilience thinking in the real world. It is an engaging and important work for anyone interested in managing risk in a complex world.